Initial Shear Modulus of Auckland Residual Soil From Field and Laboratory Tests - Norazzlina, M.Sa'don; Anas, Ibrahim; Orense, R.P; Pender, M.J. (2010)
This paper describes the experiments performed to investigate the initial shear modulus of Auckland residual soil. Firstly, WAK (wave-activated stiffness) tests and spectral analysis of surface waves (SASW) tests were conducted at a residual soil site by applying impact and harmonic loads on a circular steel plate in vertical direction. A sledgehammer equipped with a dynamic force transducer was used to produce the impact load while harmonic loading was applied using an eccentric mass shaker to generate steady-state excitations. The initial shear modulus of soil was obtained by considering the soil to be vibrating as a single degree of freedom (SDOF) system. Next, undisturbed soil samples from the site were subjected to consolidated undrained tests with three submersible miniature linear variable differential transducers (LVDTs) mounted on the sides of the specimen to measure the small strain stiffness. The LVDTs were capable of resolving displacements of less than 1 μm and measuring axial strains ranging from less then 0.001% to 2.5%. The small strain stiffness obtained from laboratory tests compared very well with those determined from geophysical tests.